Dor neuropática central e sua relação com a qualidade de vida da pessoa portadora de lesão medular traumática - Vall, Janaina (2005)
It is a cross-sectional research of analytic descriptive character exploratory, with the aim of analyzing the relationship between central neuropathic pain and life quality in the traumatic spinal cord injury individuais of the city of Fortaleza, in Ceará. For comparative effects, the data were confronted with the one of the traumatic spinal cord injury patients without pain associated. Also as specific aim to characterize the pain and your impact in the patienfs life, it was a goal of the research. They participated in the study, 32 adults paraplegic patient, linked to the general hospital, reference in traumatology, of the city of Fortaleza, that accomplished rehabilitation program in a specialized center. All possessed complete lesion, of traumatic etiology, mainly for gunshot, most was of the masculine sex, age among 20 to 47 years, illiterate or with fundamental teaching, without occupation, among 5 to 10 years of lesion. The most evident complications in the sample were neurogenic bladder and intestine, spasticity, neuropathic pain and pressure ulcer. The sample was stratified in two groups: (1) with spinal cord injury without pain and (2) with spinal cord injury and central neuropathic pain associated. The instruments used for collection of the data they were The MOS 36-item Shorts-Form Health Survey (SF-36), applied in both groups, the Questionnaire of Pain of McGilI (QDM) ally to the Numeric Visual Scale (EVN) and your complement to evaluate the impact of the pain in the patienfs life, these just applied to the group 2 (with pain). As results were found that 56,3% of the patients present central neuropathic pain as complication ofthe spinal cord injury. Of these, 50°/o make use of adjuvant medications for the treatment of the pain, even with little satisfactory effect. In relation to the characterization of the pain for the patients, these refer the burning sensation as the predominant, and this is inserted in the "sensorial" subclass of QDM, what characterizes this pain as physiopatological bases and non psicogenic. The average ofchosen descriptors was of approximately six. The pain index, also according to QDM, varied among four to 27 points and the intensity, according to EVN varied among six to seven, in most of the cases, characterizing her as moderate intensity. When analyzed the impact of the pain in the patienfs life, according to QDM, the results Show that the pain interferes directly in the activities of daily life, besides harming the social aspect. Already in relation to the behavior of the other ones in relation to the patients, these told that there are not great irritation manifestations, rage or frustration. In relation to the life quality, when the two groups are compared (with and without pain), there was no statistical significance, although the patients' scores with pain were smaller than those of patients without pain. However in the requirement quality of life versus pain index/intensity there was statistical significance in the domains "functional capacity" (p=0,005), "general State of health" (p=0,003), "mental health" (p=0,035), "pain" (p=0,003) and social aspects (p=0,006). These results demonstrate that the patient with spinal cord injury, even without neuropathic pain associated, already possesses great impairment of your life quality, when this condition comes accompanied of central neuropathic pain of index and larger intensities, this situation tends to worsen significantly. In relation to the instruments, the QDM was shown valid to evaluate the neuropathic pain, as well as SF-36 to evaluate the life quality, however, this last one possesses some limitations, sees the complexity and subjectivity of the theme.